Doubtful occurrence of Solanum nigrum L. in Bangladesh - Hassan, Md. Abul (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. Keywords: Solanum nigrum, Doubtful occurrence, Bangladesh DOI: 10.3329/bjpt.v15i1.931 Bangladesh J. Plant Taxon. 15(1): 75-76, 2008 (June)